Enterprise Architecture Zachman Framework in Ma’had Sunan Ampel Al’aly - Granita, Selvi Dwi; Sabrina, Idzni; Hidayatullah, Fifit Yulianti Amanah; Hanani, Ajib (Proceedings of the International Conference on Green Technology; Vol 10 (2019): Proceeding of International Conference on Green Technology, 2019)
Ma'had Sunan Ampel Al'aly is an educational institution under the auspices of the State Islamic University of Maulana Malik Ibrahim Malang which aims to create an academic culture to improve the religious knowledge of new students at the Maulana Malik Ibrahim State Islamic University of Malang. So far, there is no blueprint at MSAA, so it is necessary to make a blueprint as a guideline for designing the ma'Ahad system design. With the bueprint, ma'had will have system design guidelines. So that when there is a new policy it will be easier to re-plan. To create a blueprint you can use the enterprise architecture framework with the Zachman Framework method. Zachman Framework is one of the best known and used enterprise architecture frameworks. In this study the Zachman Framework was used to design the blueprint in Ma'had Sunan Ampel Al'aly.